2019
DOI: 10.3390/infrastructures4030045
|View full text |Cite
|
Sign up to set email alerts
|

Simplified Method to Estimate the Moment Capacity of Circular Columns Repaired with UHPC

Abstract: Ultra high-performance concrete (UHPC) application, to enhance the mechanical strength of axially loaded reinforced concrete bridge substructure elements, was proposed and investigated in an earlier study. The results recommended that depending on the UHPC shell thickness, this method may cause shifting of the critical section to undesired locations, due to over-strengthening of the repaired section, and this should be a design consideration. This paper proposes a new simplified analytical approach to calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…These analyses were conducted to confirm that no damage should occur in the footing section of the specimen and to predict the possible failure region since shifting of the plastic hinge was expected above the UHPC step. By comparing the moment capacity of the column section with UHPC shell and similar size conventional column, the moment capacity of the column section with UHPC shell was 18% higher than the moment capacity of the conventional column (253 kN.m (165 kip-ft) vs. 215 kN.m (158 kip-ft)) because of higher strength of UHPC shell and the additional confinement that UHPC shell provides to column concrete ( 15 , 16 ). Based on the calculations and moment ratios of these three sections, it was concluded that the failure is expected to be formed in the column section of the specimen above the UHPC step.…”
Section: Design and Construction Of Test Specimenmentioning
confidence: 97%
“…These analyses were conducted to confirm that no damage should occur in the footing section of the specimen and to predict the possible failure region since shifting of the plastic hinge was expected above the UHPC step. By comparing the moment capacity of the column section with UHPC shell and similar size conventional column, the moment capacity of the column section with UHPC shell was 18% higher than the moment capacity of the conventional column (253 kN.m (165 kip-ft) vs. 215 kN.m (158 kip-ft)) because of higher strength of UHPC shell and the additional confinement that UHPC shell provides to column concrete ( 15 , 16 ). Based on the calculations and moment ratios of these three sections, it was concluded that the failure is expected to be formed in the column section of the specimen above the UHPC step.…”
Section: Design and Construction Of Test Specimenmentioning
confidence: 97%